TAHALUF SIYASI DALAM PERSPEKTIF HUKUM ISLAM: Analisa Terhadap Kerjasama Politik Partai Islam di Malaysia - Administrator, Journal (AL-MASHALIH (Journal of Islamic Law), 2018)
This article aims to analyse the practical of tahaluf siyasi wich conducted by Islamic parties in Malaysia. Three main parties are studied in this article i.e. Partai Islam seMalaysia (PAS), Partai Amanah Negara (AMANAH) and The United Malays National Organization (UMNO). The main objective of this article is to study the concept of tahaluf siyasi in Islam and to assess whether political aliance which held by the three parties is appropriate with Islamic teaching. This study uses the library research and analysis content methods. The library reseacrh was used to obtain secondary data, while content analysis was used to analyse data. The result shows that the concept of tahaluf siyasi has appear in Islamic teaching even has practiced by Muslim since The Prophet Muhammad p.b.h era. The political aliance that hold by Islamic parties in Malaysia was not contradict with the concept of tahaluf siyasi in Islam. This political aliance model is good to be continued and emulated by another Islamic parties at another countries.